Active Tectonics in the Kvarner Region (External Dinarides, Croatia)—An Alternative Approach Based on Focused Geological Mapping, 3D Seismological, and Shallow Seismic Imaging Data - Korbar, Tvrtko; Markušić, Snježana; Hasan, Ozren; Fuček, Ladislav; Brunović, Dea; Belić, Nikola; Palenik, Damir; Kastelic, Vanja (Frontiers in Earth Science, 2020)
Active tectonics in long-lived orogenic belts usually manifests on the preexisting inherited structures. In the Kvarner region of the External Dinarides, an area with low-to-moderate seismicity related to the Adriatic microplate (Adria) northward movement, we deal with faults in predominantly carbonate rocks within tectonically complex NW-SE striking fold-and-thrust belt, which makes the identification and parametrization of the active structures challenging. Moreover, anthropogenic modifications greatly complicate access to the surface geological and geomorphological data. This paper demonstrates results of focused multidisciplinary research, from surface geological mapping and offshore shallow seismic surveys to earthquake focal mechanisms, as an active fault identification and parametrization kit, with a final goal to produce an across-methodological integrated model of the identified features in the future. Reverse, normal, and strike-slip orogen-parallel (longitudinal) to transverse faults were identified during geological mapping, but there is no clear evidence of their mutual relations and possible recent activity. The focal mechanisms calculated from the instrumental record include weak-to-moderate earthquakes and show solutions for all faulting types in the upper crust, compatible with the NE-SW oriented principal stress direction, with the stronger events favoring reverse and strike-slip faulting. The 3D spatial and temporal distribution of recent earthquake hypocenters indicate their clustering along predominantly subvertical transversal and steeply NE-dipping longitudinal planes. High-resolution shallow seismic geoacoustical survey (subbottom profiler) of the Quaternary sediments in the Rijeka Bay revealed local tectonic deformations of the stratified Late Pleistocene deposits that, along with overlaying mass-transport deposits, could imply prehistorical strong earthquake effects. Neotectonic faults onshore are tentatively recognized as highly fractured zones characterized by enhanced weathering, but there is no evidence for its recent activity. Thus, it seems that the active faults are blind and situated below the thin-skinned and highly deformed early-orogenic tectonic cover of the Adria. A strain accumulating deeper in the crust is probably irregularly redistributed near the surface along the preexisting fault network formed during the earlier phases of the Dinaric orogenesis. The results indicate a need for further multidisciplinary research that will contribute to a better seismic hazard assessment in the densely populated region that is also covered by strategic infrastructure.